SISTEM INFORMASI INVENTARIS BARANG BERBASIS WEB MENGGUNAKAN MODEL RAD PADA KANTOR KECAMATAN SUKUN - Christa Uskono, Maria; Budi Pranata, Kurriawan; Agustina, Rini (Department of System Information, 2025)
Abstract. Inventory management at Sukun District Office, Malang City. Currently, the process is done manually by recording goods using a master book and then inputting them back into the Microsoft Excel application by the district admin. This is inefficient because it is prone to data loss, difficulty in finding information, and takes a long time to make reports. The purpose of this study is to design a web-based inventory information system using the rapid application development (RAD) model at the Sukun District Office so that it can facilitate the process of data processing and monitoring inventory reports. This system is able to facilitate actors in implementing a more efficient and effective inventory system. Based on the user acceptance test (UAT) conducted, the results were 93% and it can be stated that the inventory information system is in accordance with system needs.